A systematic review of faculty development initiatives designed to enhance teaching effectiveness: A 10-year update: BEME Guide No. 40. (2nd August 2016) - Steinert, Yvonne; Mann, Karen; Anderson, Brownell; Barnett, Bonnie Maureen; Centeno, Angel; Naismith, Laura; Prideaux, David; Spencer, John; Tullo, Ellen; Viggiano, Thomas; Ward, Helena; Dolmans, Diana
Abstract: Background: This review, which focused on faculty development initiatives designed to improve teaching effectiveness, synthesized findings related to intervention types, study characteristics, individual and organizational outcomes, key features, and community building. Methods: This review included 111 studies (between 2002 and 2012) that met the review criteria. Findings: Overall satisfaction with faculty development programs was high. Participants reported increased confidence, enthusiasm, and awareness of effective educational practices. Gains in knowledge and skills, and self-reported changes in teaching behaviors, were frequently noted. Observed behavior changes included enhanced teaching practices, new educational initiatives, new leadership positions, and increased academic output. Organizational changes were infrequently explored. Key features included evidence-informed educational design, relevant content, experiential learning, feedback and reflection, educational projects, intentional community building, longitudinal program design, and institutional support. Conclusion: This review holds implications for practice and research. Moving forward, we should build on current success, broaden the focus beyond individual teaching effectiveness, develop programs that extend over time, promote workplace learning, foster community development, and secure institutional support. We should also embed studies in a theoretical framework, conduct more qualitative and mixed methods studies, assess behavioral and organizational change, evaluate transfer to practice, analyse key features, and explore the role of faculty development within the larger organizational context.